PENERAPAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA - ENI SETIYANINGSIH DWI ASTUTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to determine the effectiveness of the learning model using the Problem Based Learning learning model in improving student achievement in Biology subjects in class XI MIPA1 students of SMA Negeri 1 Lendah in the even semester of the 2021/2022 academic year. In this study, data were taken from observations during learning, the activeness of students in discussions, collaborating and expressing opinions and test results, this data was analyzed descriptively qualitatively. The results of this study are indicated by student learning evaluation data which has increased from pre-cycle, cycle 1 and cycle 2. In the pre-test results in the pre-cycle students are able to achieve the Minimum Completeness Criteria of 31.43%, in cycle 1 reach the Minimum Completeness Criteria of 74 .29% and in cycle 2 achieved the Minimum Completeness Criteria of 94.29%. The results of student observations also increased from cycle 1 and cycle 2. Cycle 1 Meeting 1 reached 79.05%, meeting 2 in cycle 1 reached 81.07%, meeting 1 in cycle 2 reached 84.64% and meeting 2 in cycle 2 reached 95 ,71%. The results of the study indicate that learning using the Problem Based Learning model can improve learning outcomes of Biology, especially Respiration and can increase student activity and responsibility so that students will master the subject matter and will get high learning outcomes. ABSTRACTPenelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran dengan menggunakan model pembelajaran Problem Based Learning dalam meningkatkan prestasi belajar siswa pada mata pelajaran Biologi pada peserta didik kelas XI MIPA1 SMA Negeri 1 Lendah semester genap tahun pelajaran 2021/2022. Dalam penelitian ini data diambil dari observasi pada saat mengikuti pembelajaran, keaktifan peserta didik dalam diskusi, berkerjasama dan menyampaikan pendapat dan hasil tes, data ini dianalisis secara diskriptif kualitatif. Hasil penelitian ini ditunjukkan dengan data evaluasi belajar siswa yang mengalami peningkatan dari pra siklus, siklus 1 dan siklus 2. Pada hasil pre test di pra siklus siswa mampu mencapai Kriteria Ketuntasan Minimal sebesar 31,43%, pada siklus 1 mencapai Kriteria Ketuntasan Minimal sebesar 74,29% dan pada siklus 2 mencapai Kriteria Ketuntasan Minimal sebesar 94,29%. Untuk hasil observasi siswa juga mengalami peningkatan dari siklus 1 dan siklus 2. Siklus 1 Pertemuan 1 mencapai 79,05%, pertemuan 2 siklus 1 mencapai 81,07%, pertemuan 1 siklus 2 mencapai 84,64% dan pertemuan 2 siklus 2 mencapai 95,71%. Hasil penelitian menunjukkan bahwa pembelajaran menggunakan model Problem Based Learning dapat meningkatkan hasil belajar Biologi khususnya Respirasi serta dapat meningkatkan keaktifan dan tanggung jawab siswa sehingga siswa akan menguasai materi pelajaran dan akan mendapat hasil belajar yang tinggi.